Pancreatic peptide hormone expression in the RINm5F cell line - Van der Merwe, Elizabeth Lael (Division of Cell Biology, 2024)
Phenotypic heterogeneity is a striking feature of the pancreatic islet cell lines (RIN and MSL) derived from a rat islet cell tumour (Chick et al., 1977) which may therefore be suitable for the study of islet cell differentiation in vitro. In the present study, the RINm5F cell line (Oie ~-, 1983) was investigated to determine whether or not it would be suitable for this purpose. This study presents the results from work aimed at determining which hormone-producing phenotypes were expressed under routine and modified culture conditions. Insulin, detected by immunoperoxidase labelling at earlier passages, was not detectable in later passages of RINm5P:-MRC cultures. Immunoblots and radio-immunoassay performed on cell extracts and culture medium respectively confirmed that RINm5F cells contained proinsulin and that low levels of insulin and/ or proinsulin were secreted into the medium. These findings suggested that the insulin content of individual cells was at the lower limit of detection for the immunoperoxidase technique. To overcome the problem of detecting and quantifying the number of cells containing low levels of insulin by microscopy, a protocol was established for immunolabelling cell suspensions for analysis by flow cytometry. Flow cytometry confirmed that RINm5F cultures contained a small percentage (less than 2%) of cells stained for insulin and that a greater subpopulation of cells (18-38%) were positively stained for insulin after cultures had been exposed to 2mM sodium butyrate for three days. Although positively stained cells were observed by immunoperoxidase or immunofluorescence microscopy in sodium butyrate-treated cultures, staining was barely above that of background staining in peroxidasestained preparations and positively labelled cells could only be identified at high magnification in fluorescent-stained preparations. Thus flow cytometry successfully provided an alternative approach to accurately quantify insulin expression in RINm5F-MRC cells. Flow cytometry, immunoblotting and immunocytochemistry established that all glucagon and somatostatin-like immunoreactivity in RINm5F cultures was non-specific and was most likely caused by the binding of non-specific components present in rabbit serum. Ultrastructural studies confirmed that morphologically differentiated islet cell phenotypes were not present in RINm5F-MRC cultures. The finding that RINm5F-MRC cultures consisted mainly of agranular cells and that only a small subpopulation of cells stained for insulin, indicates that this cell line appears to be poorly differentiated. However, the increase in the number of cells containing insulin and the increased insulin secretion in response to sodium butyrate shows that at least some of these cells have the potential to differentiate. These results indicate that RINm5F-MRC cells are suitable for the study of /1-cell differentiation. It remains to be determined whether or not they are suitable for studying the differentiation of other pancreatic islet cell types.